Perceived cardiovascular disease risk and tailored communication strategies among rural and urban community dwellers in Rwanda: a qualitative study - Jean Berchmans Niyibizi; Kufre Joseph Okop; Jean Pierre Nganabashaka; Ghislaine Umwali; Stephen Rulisa; Seleman Ntawuyirushintege; David Tumusiime; Alypio Nyandwi; Evariste Ntaganda; Peter Delobelle; Naomi Levitt; Charlotte M. Bavuma (BMC Public Health, 2022)
Abstract Background In Rwanda, cardiovascular diseases (CVDs) are the third leading cause of death, and hence constitute an important public health issue. Worldwide, most CVDs are due to lifestyle and preventable risk factors. Prevention interventions are based on risk factors for CVD risk, yet the outcome of such interventions might be limited by the lack of awareness or misconception of CVD risk. This study aimed to explore how rural and urban population groups in Rwanda perceive CVD risk and tailor communication strategies for estimated total cardiovascular risk. Methods An exploratory qualitative study design was applied using focus group discussions to collect data from rural and urban community dwellers. In total, 65 community members took part in this study. Thematic analysis with Atlas ti 7.5.18 was used and the main findings for each theme were reported as a narrative summary. Results Participants thought that CVD risk is due to either financial stress, psychosocial stress, substance abuse, noise pollution, unhealthy diets, diabetes or overworking. Participants did not understand CVD risk presented in a quantitative format, but preferred qualitative formats or colours to represent low, moderate and high CVD risk through in-person communication. Participants preferred to be screened for CVD risk by community health workers using mobile health technology. Conclusion Rural and urban community members in Rwanda are aware of what could potentially put them at CVD risk in their respective local communities. Community health workers are preferred by local communities for CVD risk screening. Quantitative formats to present the total CVD risk appear inappropriate to the Rwandan population and qualitative formats are therefore advisable. Thus, operational research on the use of qualitative formats to communicate CVD risk is recommended to improve decision-making on CVD risk communication in the context of Rwanda.